Disarrangement of Fiber Tracts and Decline of Neuronal Density Correlate in Glioma Patients—A Combined Diffusion Tensor Imaging and 1H-MR Spectroscopy Study - Goebell, E.; Fiehler, J.; Ding, X.-Q.; Paustenbach, S.; Nietz, S.; Heese, O.; Kucinski, T.; Hagel, C.; Westphal, M.; Zeumer, H. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Diffusion tensor imaging (DTI) and MR spectroscopy are noninvasive, quantitative tools for the preoperative assessment of gliomas with which the quantitative parameter fractional anisotropy (FA) and the concentration of neurometabolites N-acetylaspartate (NAA), choline (Cho), creatine (Cr) of the brain can be determined. Measurements of FA and NAA reflect the integrity of fiber tracts and the presence of neurons, respectively. This investigation examines changes of FA and NAA and compares these different aspects in architecture of gliomas after spatial coregistration.METHODS: DTI and chemical shift 1H-MR spectroscopy was performed in 34 healthy volunteers and 69 patients with histologically confirmed (n = 48) or morphologically suspected (n = 21) non-necrotic brain glioma. Volumes of interest (VOIs) were placed in the tumor center (TC), the tumor border (TB), the normal-appearing white matter adjacent to the tumors (TNWM), and in the white matter of the contralateral hemisphere (NWMC). Median FA values and NAA/Cr and NAA/Cho ratios were calculated in the patients’ VOIs and the gray and white matter of the volunteers. Correlations of FA values and NAA ratios were calculated.RESULTS: Continuous changes of FA and NAA from the tumor center to the periphery (the adjacent white matter and the contra-lateral hemisphere, respectively) were observed, where median values were: TC: 0.73 ± 0.45, 0.47 ± 0.58, 0.17 ± 0.15 (NAA/Cr, NAA/Cho, FA); TB: 1.06 ± 0.53, 1.00 ± 0.15, 0.23 ± 0.08; TNWM: 1.42 ± 2.48, 1.21 ± 0.95, 0.34 ± 0.09; and NWMC: 1.63 ± 0.72, 1.56 ± 1.34, 0.38 ± 0.08. Correlation of median FA values and NAA ratios in the cumulative group of patients was high (r = 0.99 [NAA/Cr], 0.95 [NAA/ Cho] at P < .01). Correlation between the individual NAA ratios and the FA values was moderate (r = 0.53 [NAA/Cr], 0.51 [NAA/Cho] at P < .01).CONCLUSION: In gliomas, the degree of tissue organization decreases continuously from the surrounding tissue toward the center of the tumor accompanied by a concordant decrease of NAA. This uniform behavior of FA and NAA reflects a decreasing integrity of both neuronal structures and fibers.